2009
DOI: 10.1111/j.1365-2133.2008.08852.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of primary cutaneous T-cell lymphoma in Norway

Abstract: The incidence of both CTCL and MF/SS increased in Norway during the period 1980-2003.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 13 publications
0
31
0
4
Order By: Relevance
“…Based on recent analyses, the incidence of this cancer during 2000–2010 years reached ~10 cases per million individuals per year in the United States . Similarly, increase in CTCL incidence has been observed in other parts of the world . This malignancy often presents at an older age (i.e., >55 years old) in Caucasians, but in African‐American, Hispanic, and Middle‐Eastern individuals studies have shown an earlier age at presentation with a more aggressive clinical course .…”
Section: Introductionmentioning
confidence: 97%
“…Based on recent analyses, the incidence of this cancer during 2000–2010 years reached ~10 cases per million individuals per year in the United States . Similarly, increase in CTCL incidence has been observed in other parts of the world . This malignancy often presents at an older age (i.e., >55 years old) in Caucasians, but in African‐American, Hispanic, and Middle‐Eastern individuals studies have shown an earlier age at presentation with a more aggressive clinical course .…”
Section: Introductionmentioning
confidence: 97%
“…6 in 1980-1984 to 2.9/1 000 000 in 2000-2003 in Norway 4. Comparison of percentage of subtypes of CTCL and CBCL of our study with the international literature.…”
mentioning
confidence: 56%
“…1,4 The literature suggests that MF incidence may be increasing, but this may be an artifact due to improved diagnostic methods. 5,6 However, it is still an uncommon disorder, with approximately 0.18/100,000 person-years in Norway, for example. 6 A wide variety of treatment options is available, often tailored to a patient's stage and individual circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 However, it is still an uncommon disorder, with approximately 0.18/100,000 person-years in Norway, for example. 6 A wide variety of treatment options is available, often tailored to a patient's stage and individual circumstances. 2 These options include corticosteroids, retinoids, bexarotene, PUVA, interferon-α, interferon-γ, and biologics (alemtuzumab), amongst others.…”
Section: Discussionmentioning
confidence: 99%